2010
DOI: 10.1103/physrevb.82.195410
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of interface structure and energetics in semicoherentFe(001)/MX(001)systems (

Abstract: We perform a systematic ab initio study of the electronic and atomic structure of semicoherent interfaces between bcc Fe and NaCl MX ͑M = Sc, Ti, V, Cr, Zr, Nb, Hf, Ta; X = C or N͒. The interface energetics is accessed by using a Peierls-Nabarro framework, in which ab initio data for the chemical interactions across the interface are combined with a continuum description to account for the elastic distortions. The key factors to the trends in the interface energy are identified and discussed with respect to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
28
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(33 citation statements)
references
References 73 publications
5
28
0
Order By: Relevance
“…where M = 3 is the matrix orientation factor, b = 0.286 nm is Burgers vector, c is the matrix-particle interface energy assumed for the Fe-NbC interface to be c = 1 Jm À2 , [44] and f is the particle volume fraction. The variation in precipitation strengthening (Table III) followed the trend for particle volume fraction in the corresponding particle size ranges (Table I): for >20 nm particles, the maximum precipitation strengthening contribution was observed for the 1248 K (975°C) temperature schedule; and for <20 nm particles, the contribution decreased with a decrease in the finish deformation temperature.…”
Section: Effect Of Strengthening Mechanisms On the Yield Stressmentioning
confidence: 99%
See 2 more Smart Citations
“…where M = 3 is the matrix orientation factor, b = 0.286 nm is Burgers vector, c is the matrix-particle interface energy assumed for the Fe-NbC interface to be c = 1 Jm À2 , [44] and f is the particle volume fraction. The variation in precipitation strengthening (Table III) followed the trend for particle volume fraction in the corresponding particle size ranges (Table I): for >20 nm particles, the maximum precipitation strengthening contribution was observed for the 1248 K (975°C) temperature schedule; and for <20 nm particles, the contribution decreased with a decrease in the finish deformation temperature.…”
Section: Effect Of Strengthening Mechanisms On the Yield Stressmentioning
confidence: 99%
“…For the measured particle volume fractions (Table I) and the unit cell sizes a Ti3Nb1C2N2 = 0.64 nm (on average from [42] ), a NbC = 0.44 nm, [43][44][45] and a bccFe = 0.286 nm, the C contents in all particles were calculated to be 0.063 at. pct (0.014 wt pct), 0.068 at.…”
Section: Effect Of Strengthening Mechanisms On the Yield Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Johansson et al developed a method for determining the interface energy using a few points of γ surface [18][19][20]. They showed that the strain energy should be relieved by forming a semi-coherent precipitate for thicker precipitates, since the elastic energy caused by the coherent strain increases with the thickness of the precipitate.…”
Section: Introductionmentioning
confidence: 99%
“…Many first-principles calculations have been performed for the interfaces between body-centered cubic (bcc) iron and carbide or nitride precipitates with an NaCl-type structure [10][11][12][13][14][15][16][17][18][19][20], and the bonding nature between these interfaces has been discussed in the literature. Hartford investigated the chemical bond across the interface and interface energies for the coherent interface between VN and bcc iron [10].…”
Section: Introductionmentioning
confidence: 99%